THE RELATIONSHIP BETWEEN PHYSICAL ACTIVITY AND OBESITY BASED ON BODY FAT PERCENTAGE IN BANJAROYO VILLAGE, KALIBAWANG, KULON PROGO, D.I. YOGYAKARTA - Sesilia Effendy; Maria Felicia Gunawan; Daniel Lintang Adhi Argoputra; YB Abraham; Patricia Dian Anggraeni; Fenty Fenty (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2018)
Obesity, a metabolic disorder characterized by the accumulation of excessive body fat, which is closely associated with metabolic derangement-related disease. Obesity can be caused by low physical activity that can be assessed using body fat percentage. The purpose of this study was to identify the relationship between physical activity and obesity based on body fat percentage in Banjaroyo village, Kalibawang, Kulon Progo, Special Region of Yogyakarta. This study was an observational-analytical study with cross sectional design and conducted in January-June 2017. Total samples were 243 people (86 males and 157 females) with age range between 18-65 years old. Physical activity data were collected using a structured interview based on International Physical Activity Questionnaire (IPAQ), while body fat percentage was taken using Bioelectrical Impedance Analysis (BIA). The data were analyzed using comparative Chi-square test with the level of significance of 95%. The prevalence of obesity based on body fat percentage was 78.2% and 21.8% in men and women, respectively. Results of the study showed that there is no significant relationship between physical activity and obesity based on body fat percentage (p=0.419; CI 95%: 0.66-2.689). In conclusion, there is no significant relationship between physical activity and incidence of obesity.